2014
DOI: 10.1007/s00214-013-1441-x
|View full text |Cite
|
Sign up to set email alerts
|

The V state of ethylene: valence bond theory takes up the challenge

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. Further improvement to 7.96/7.93 eV is achieved at the variational and diffusion Monte Carlo (MC) levels, respectively, VMC/DMC, using a Jastrow factor coupled with the same compact VB wave function. Furthermore, the measure of the spat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 57 publications
(91 reference statements)
1
41
0
1
Order By: Relevance
“…The EOM-CCSDT excitation energy in the same basis set was reported to be 7.89 eV. The authors concluded that nonadiabatic effects were important in shifting the vertical excitation energy to higher energy than the experimental observed band maximum, in disagreement with the findings of Müller et al 52 In 2014 Wu et al 70 used the valence bond self consistent field (VBSCF) and breathing orbital valence bond (BOVB) methods with several basis sets. V state T v values ranged from 9.…”
Section: A Theorymentioning
confidence: 94%
“…The EOM-CCSDT excitation energy in the same basis set was reported to be 7.89 eV. The authors concluded that nonadiabatic effects were important in shifting the vertical excitation energy to higher energy than the experimental observed band maximum, in disagreement with the findings of Müller et al 52 In 2014 Wu et al 70 used the valence bond self consistent field (VBSCF) and breathing orbital valence bond (BOVB) methods with several basis sets. V state T v values ranged from 9.…”
Section: A Theorymentioning
confidence: 94%
“…Ethylene S 1 surface is a specially challenging problem, starting from (i) the adequate computation of the excitation into the V state [6], then (ii) the description of the right topography of the state, which includes a crossing with the Z state near the twisted structure and a conical intersection at twisted-pyramidalized geometries Surface Hopping Dynamics with DFT Excited States [115], to finally (iii) the dynamics evolution itself, which has motivated a long debate between theorists and experimentalists [117][118][119]. In fact, Levine et al [120] have used maps similar to those in Fig.…”
Section: Critical Appraisalmentioning
confidence: 99%
“…Not only are such values of the order of magnitude of many reaction barriers, but also these errors are unevenly distributed among several states for the same method and tend to grow bigger out of the Franck-Condon region. Well known examples are the relatively large errors of the energy of ionic states predicted by truncated ab initio configuration interaction [6] or of the energy of charge-transfer states of time-dependent density functional theory with conventional functionals [7].…”
Section: Introductionmentioning
confidence: 99%
“…The allyl cases are possibly simple cases, but they give the opportunity to test how symmetry is accounted for while no constraint is provided. The ethene case is a reputedly difficult case from the MO point of view, and was recently considered at the VB level …”
Section: Resultsmentioning
confidence: 99%
“…The literature on ethene's excited states, and particularly on the V state (1 1 B 1u ), is very rich, and the recent paper published last year by Feller et al provides a detailed survey of the subject, particularly in their Supporting Information. To put it in a nutshell, the ground state (1 1 A g ) is called the N state, and the 1 B 1u excited state is called the V state . The V state is reputedly difficult to describe due to some mixing with a Rydberg state of same symmetry (2 1 B 1u ), and the starting orbitals are of great importance.…”
Section: Allylsmentioning
confidence: 99%